THE PORTRAIT OF EDUCATIONAL PHILOSOPHY THROUGH AN ANALYSIS OF INDONESIAN MOVIE BASED ON PESANTREN THEME - Aini, Devi Nur; Shofi, Millatus; Zuhriya, Latifatu (Nurul Jadid University, 2022)
The way of people educate and think of their values affect the educational system; it is found in Pesantren as the Islamic institution that holds norm, belief, and values in education system. Meanwhile, movies is one of the effective devices to promote the society learning process due to its popularity among the society, teenagers and also adults. Many movies produced intended to portray the uniqueness of educational system in pesantren and got a great attention as educational philosophy. This study examined the habits, norm, and values of educational system through the analysis of the movie Negeri 5 Menara. Document review and descriptive analysis method used as a qualitative research methods. Film observation form gathered and the decoding process of it prior to the scene identification was based on education and specific themes. The results shown by the setting, gesture, and action of each character among the other, and some of the quotation based on some verses in Al-Qur’an to improve reliability. The Findings depicted that perennials was identified as the most prominent educational philosophy up to nowadays. The central leading character plays a part of students’ belief in seeking knowledge. It is said in Javanese language as “Ngalap barokahe Kyai”.